2012
DOI: 10.1890/11-0935.1
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood effects on seed dispersal by frugivores: testing theory with a mistletoe–marsupial system in Patagonia

Abstract: Abstract. The outcome of the dispersal process in zoochorous plants is largely determined by the behavior of frugivorous animals. Recent simulation studies have found that fruit removal rates and mean dispersal distances are strongly affected by fruiting plant neighborhoods. We empirically tested the effects of conspecific fruiting plant neighborhoods, crop sizes, and plant accessibility on fruit removal rates and seed dispersal distances of a mistletoe species exclusively dispersed by an arboreal marsupial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 45 publications
0
61
0
2
Order By: Relevance
“…In neighborhoods with many fruiting species, crop size is an important variable for predicting fruit removal-the larger the crop size the higher the fruit removal (Morales et al, 2012). There are two primary hypotheses to explain how crop size and the spatial aggregation of fruiting plants may influence fruit removal by vertebrates: the competition hypothesis and the facilitation hypothesis (Sargent, 1990).…”
Section: Neighborhood Effectsmentioning
confidence: 99%
“…In neighborhoods with many fruiting species, crop size is an important variable for predicting fruit removal-the larger the crop size the higher the fruit removal (Morales et al, 2012). There are two primary hypotheses to explain how crop size and the spatial aggregation of fruiting plants may influence fruit removal by vertebrates: the competition hypothesis and the facilitation hypothesis (Sargent, 1990).…”
Section: Neighborhood Effectsmentioning
confidence: 99%
“…For example, frugivorous birds are commonly shown to use cover-rich neighbourhoods (e.g. Morales et al 2012) and therefore more seeds are expected to be dispersed under forest patches compared to open areas (Herrera and García 2010). However, despite many insights having been gained to date, knowledge of how landscape structure influences frugivore-mediated seed dispersal patterns in heterogeneous landscapes-particularly those generated by frugivore guilds other than birds-, is still limited (Herrera and Doblas-Miranda 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope ratios can also be used to estimate the proportion of a 'batch' of dispersed seeds (e.g. in a seed trap or fecal clump) that originated from a labeled source plant or patch, as Morales et al (2012) demonstrated in their study of mistletoe dispersal, by grinding seeds together and analyzing the isotopic signal with a Bayesian mixing model. …”
Section: Resultsmentioning
confidence: 99%